Enhancing Business Performance through Green Investment and Marketing with Mediating Influence of Corporate Social Responsibility - Rida Fatima; Hafiz Mohsin Ali; Maryam Ibrar (Minhaj International Journal of Economics and Organization Sciences, 2025)
Organizations worldwide have continued their relentless extraction of natural resources in their profit-seeking activities without showing any regard for the environmental sustainability. However, it is now high time for businesses to admit the vital role of the environment in our lives and give back to society what it deserves. With the alarming rise of health hazards caused by ecological pollution, it has become imperative for Pakistan's business hub to embrace a green approach. Here the objective is to observe how green investment impacts business performance in the Pakistani corporate sector considering corporate social responsibility working as a mediating factor. This study utilized a quantitative methodology to collect primary data from over 50 companies through questionnaire surveys, employing a 5-point Likert scale to evaluate industrial, service, and manufacturing sectors. The survey was conducted to understand their perspective on the impact of green investment & advertising on their business performance. The findings demonstrated that the sustainable procedures like Green Marketing and Green Investment positively influence the performance of the firm while maintaining the environment. The essential role of Corporate Social Responsibility (CSR) in connecting these green initiatives to sustainable performance is evident, particularly within Pakistan's corporate hub focused on environmental preservation. This research offers a valuable framework for firms, managers, experts, and other officials to comprehend and effectively manage green marketing, investments, and corporate social responsibility (CSR) in order to enhance business performance.